Alteration of network connectivity in stroke patients with apraxia of speech after tDCS: A randomized controlled study - Zhao, Jiayi; Li, Yuanyuan; Zhang, Xu; Yuan, Ying; Cheng, Yinan; Hou, Jun; Duan, Guoping; Liu, Baohu; Wang, Jie; Wu, Dongyu (Frontiers in Neurology, 2022)
Objective This study aimed to examine the changes in the functional connectivity of the cortical speech articulation network after anodal transcranial direct current stimulation (A-tDCS) over the left lip region of the primary motor cortex (M1) in subacute post-stroke patients with apraxia of speech (AoS), and the effect of A-tDCS on AoS. Methods A total of 24 patients with post-stroke AoS were randomized into two groups and received A-tDCS over the left lip region of M1 (tDCS group)/ sham tDCS (control group) as well as speech and language therapy two times per day for 5 days. Before and after the treatment, the AoS assessments and electroencephalogram (EEG) were evaluated. The cortical interconnections were measured using the EEG non-linear index of cross approximate entropy (C-ApEn). Results The analysis of EEG showed that, after the treatment, the activated connectivity was all in the left hemisphere, and not only regions in the speech articulation network but also in the dorsal lateral prefrontal cortex (DLPFC) in the domain-general network were activated in the tDCS group. In contrast, the connectivity was confined to the right hemisphere and between bilateral DLPFC and bilateral inferior frontal gyrus (IFG) in the control group. In AoS assessments, the tDCS group improved significantly more than the control group in four of the five subtests. The results of multivariate linear regression analyses showed that only the group was significantly associated with the improvement of word repetition (P = 0.002). Conclusion A-tDCS over the left lip region of M1 coupled with speech therapy could upregulate the connectivity of both speech-specific and domain-general networks in the left hemisphere. The improved articulation performance in patients with post-stroke AoS might be related to the enhanced connectivity of networks in the left hemisphere induced by tDCS. Clinical trial registration ChiCTR-TRC-14005072.